Accelerated carbonation technology for enhanced treatment of recycled concrete aggregates: A state-of-the-art review. (3rd May 2021) - Pu, Yunhui; Li, Lang; Wang, Qingyuan; Shi, Xiaoshuang; Luan, Chenchen; Zhang, Guomin; Fu, Ling; El-Fatah Abomohra, Abd
Highlights: Reaction processes and factors of accelerated carbonation are summarized. The quality of carbonated recycled concrete aggregates (RCAs) is evaluated. The performance of concrete incorporating carbonated RCAs are discussed. Environmental impacts and economic feasibility are analyzed. Abstract: The accelerated carbonation technology has been utilized in order to enhance the properties of the recycled concrete aggregates (RCAs) and efficient sequestration of carbon dioxide. Numerous studies have been conducted on this developing technology, while there are few systematic reviews on this method. In the present paper, the reaction processes, influencing factors and mechanisms of the accelerated carbonation to treat RCAs are summarized. The quality of carbonated RCAs and the properties of concrete incorporating carbonated RCAs are evaluated. Moreover, the environmental impacts and economic feasibility of this technique are analyzed. Results showed that carbon dioxide could react with calcium hydroxide, calcium silicate hydrates and other calcium substances in RCAs leading to the precipitation of calcium carbonate. The carbonation processes were mainly determined by carbonation conditions and RCAs characteristics. Carbonated RCAs exhibited lower water absorption, lower crush value and higher apparent density than the non-carbonated ones. The mechanical properties and durability of the concrete containing carbonated RCAs were also improved significantly. This technology has been also confirmed an environmentally friendly and economically feasible method. Finally, some research perspectives on this technology are presented.